Preschool Teachers Perspectives on Outdoor Play Among Malaysia’s Preschoolers - Chiew, Gek Yim,; Yunus, Hashimah Mohd (Journal of Ecohumanism, 2024)
This study investigates the significance of outdoor play environments for preschool children in Malaysia. Utilizing a qualitative approach, the research explores how preschool teachers and children promote outdoor activities within school curricula, while also examining barriers and concerns surrounding outdoor play provision. While international research suggests weather significantly influences perceptions of outdoor play, limited Malaysian perspectives exist. This study addresses this gap by exploring the perspectives of Malaysian preschool teachers, parents, and children, discussing strategies for promoting outdoor learning. Focusing on the physical, emotional, and well-being dimensions associated with young children’s physical activity, the study highlights the importance of outdoor play in their learning and development. It examines how practitioners and parents perceive outdoor play, analyzes barriers hindering its provision, and assesses whether these barriers justify limited outdoor play opportunities. Findings reveal distinct perspectives on outdoor play between teachers and parents, yet a shared recognition of its importance and benefits. The study also identifies concerns regarding potential risks associated with insufficient physical activity and reflects on adult awareness and involvement in promoting outdoor play. Notably, the research incorporates children’s voices, ensuring their perspectives are acknowledged and valued. This study has implications for early childhood teachers’ practices and offers recommendations for future research. It aims to encourage increased outdoor play integration in preschools and motivate Early Childhood Care and Education (ECCE) organizations to prioritize outdoor learning. By exploring practitioner and parental perspectives on the importance of outdoor play and examining how adults plan and promote it in children’s lives, this research contributes valuable knowledge to the field of early childhood education.